Association of Refractive Errors with Axial Length and Anterior Chamber Depth in Different Age Groups: Doi: 10.36351/pjo.v40i4.1838 - Siddiqui, Farnaz; Alkhairy, Saba; Asad Azeem Mirza; Muhammad Nizamuddin; Baig, Mahad (Pakistan Journal of Ophthalmology, 2024)
Purpose: To determine association of refractive errors with axial length and anterior chamber depth in different age groups. Study Design: Cross-sectional study. Place and Duration of Study: Ophthalmology Department of Dow University Hospital (Ojha campus),Dow International Medical College, Dow University of Health Sciences, Karachi, Pakistan from October 2020 to December 2020. Methods: Eighty-three individuals of different age groups ranging from 11-80 years were included in the study.Ocular measurements including refractive error, axial length, and anterior chamber depth were determined in all participants. The association of refractive error with anterior chamber depth and axial length was tested by using two independent sample t test, Mann-Whitney U test and ANOVA. Results: Among 83 individuals, males were 42.2% (n=35) and females were 57.8% (n=48). Most common type of refractive error was astigmatism which was found in 48.2% (n=40) participants. The overall average depth of anterior chamber (mm) and average axial length (mm) were 3.11±0.39 and 23.27±0.87 respectively. Mean differences in anterior chamber depth were statistically significant among different age groups . Statistically significant differences in mean axial length were found among different refractive errors . Conclusion: These results show a significant relation of different refractive errors with axial length and anterior chamber depth and it can be helpfulin explaining the risk factors of different ocular diseases as well asit can also be helpful in clinical and diagnostic purposes in ophthalmology.